Efektivitas Penggunaan Aplikasi Lamikro pada Pengelolaan Keuangan Usaha Mikro Kecil dan Menengah (UMKM) di Kecamatan Buleleng - Shara Widya; Made Pradana Adiputra (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aimed to measure the use of Lamikro application in the financial management of MSME (Micro Small and Medium Enterprises) in Buleleng District and the interest of MSME players in using Lamikro application. This study used mixed methods. The population of this study was 153 MSME players in Buleleng District who already have IUMK (micro and small enterprise license). The technique of determining the sample was the purposive sampling technique. Methods of data collection were done through questionnaires, observation, and interviews. The effectiveness of using Lamikro application was based on indicators of data security, speed (time), accuracy, variety of reports, relevance, accuracy, information quality, data independence, data standardization, and data integration using descriptive statistical analysis of frequency measures. Meanwhile, the interest of MSME players in using this application was obtained through interviews with several MSME players. The results showed that the use of Lamikro application in MSME financial management in Buleleng District has been effective in producing financial reports according to the needs of MSME players and most of them had an interest in using Lamikro application.